Evolution of anti-malaria policies and measures in P.R. China for achieving and sustaining malaria-free - Yin, Jian-Hai; Zhang, Li; Feng, Xin-Yu; Xia, Zhi-Gui (Frontiers in Public Health, 2023)
Malaria is a major public health threat worldwide, and it was also widely prevalent in the history in China, seriously endangering people's health and affecting socioeconomic development. China was certified malaria elimination in 2021 with unremitting efforts since the founding of the People's Republic of China in 1949. This great achievement has been another milestone in the fight against major infectious diseases following the elimination of smallpox, poliomyelitis, leprosy, filariasis, neonatal tetanus and blinding trachoma in China. This paper briefly introduces the malaria burden dynamics and the corresponding malaria transmission risk stratificantions, as well as systematically reviews the evolution of anti-malaria policies and measures from severe epidemic to elimination in China. Meanwhile, five key lessons in malaria control and elimination in China are also briefly summarized. All of the above provide evidences for promoting global malaria eradication and preventing reestablishment of malaria transmission, finally benefit all individuals still suffering from the scourge of malaria.